Targeting of the Lipid Metabolism Impairs Resistance to BRAF Kinase Inhibitor in Melanoma - Vergani, Elisabetta; Beretta, Giovanni L.; Aloisi, Mariachiara; Costantino, Matteo; Corno, Cristina; Frigerio, Simona; Tinelli, Stella; Dugo, Matteo; Accattatis, Felice Maria; Granata, Agnese; Arnaboldi, Lorenzo; Rodolfo, Monica; et al. (Frontiers in Cell and Developmental Biology, 2022)
Drug resistance limits the achievement of persistent cures for the treatment of melanoma, in spite of the efficacy of the available drugs. The aim of the present study was to explore the involvement of lipid metabolism in melanoma resistance and assess the effects of its targeting in cellular models of melanoma with acquired resistance to the BRAF-inhibitor PLX4032/Vemurafenib. Since transcriptional profiles pointed to decreased cholesterol and fatty acids synthesis in resistant cells as compared to their parental counterparts, we examined lipid composition profiles of resistant cells, studied cell growth dependence on extracellular lipids, assessed the modulation of enzymes controlling the main nodes in lipid biosynthesis, and evaluated the effects of targeting Acetyl-CoA Acetyltransferase 2 (ACAT2), the first enzyme in the cholesterol synthesis pathway, and Acyl-CoA Cholesterol Acyl Transferase (ACAT/SOAT), which catalyzes the intracellular esterification of cholesterol and the formation of cholesteryl esters. We found a different lipid composition in the resistant cells, which displayed reduced saturated fatty acids (SFA), increased monounsaturated (MUFA) and polyunsaturated (PUFA), and reduced cholesteryl esters (CE) and triglycerides (TG), along with modulated expression of enzymes regulating biosynthetic nodes of the lipid metabolism. The effect of tackling lipid metabolism pathways in resistant cells was evidenced by lipid starvation, which reduced cell growth, increased sensitivity to the BRAF-inhibitor PLX4032, and induced the expression of enzymes involved in fatty acid and cholesterol metabolism. Molecular targeting of ACAT2 or pharmacological inhibition of SOAT by avasimibe showed antiproliferative effects in melanoma cell lines and a synergistic drug interaction with PLX4032, an effect associated to increased ferroptosis. Overall, our findings reveal that lipid metabolism affects melanoma sensitivity to BRAF inhibitors and that extracellular lipid availability may influence tumor cell response to treatment, a relevant finding in the frame of personalized therapy. In addition, our results indicate new candidate targets for drug combination treatments.